2011
DOI: 10.1371/journal.pone.0021495
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling Reveals MiRNA Families Regulating Specific Biological Pathways in Mouse Frontal Cortex and Hippocampus

Abstract: MicroRNAs (miRNAs) are small regulatory molecules that cause post-transcriptional gene silencing. Although some miRNAs are known to have region-specific expression patterns in the adult brain, the functional consequences of the region-specificity to the gene regulatory networks of the brain nuclei are not clear. Therefore, we studied miRNA expression patterns by miRNA-Seq and microarrays in two brain regions, frontal cortex (FCx) and hippocampus (HP), which have separate biological functions. We identified 354… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 63 publications
4
65
0
Order By: Relevance
“…In chicken, sex-dependent differential regulation of the 2 arms of miR-202 has been reported [Bannister et al, 2009]. Similarly, several miRNA families were differentially expressed in 2 regions of mouse brain [Juhila et al, 2011]. In the present study, we found differential expression of miRNAs within families and miRNA arms between tissues and sexes in a teleost, which could result from target preference of miRNAs as it has been previously shown in mammals [Juhila et al, 2011].…”
Section: Sex-biased Expression Of Conserved Mirnassupporting
confidence: 85%
See 1 more Smart Citation
“…In chicken, sex-dependent differential regulation of the 2 arms of miR-202 has been reported [Bannister et al, 2009]. Similarly, several miRNA families were differentially expressed in 2 regions of mouse brain [Juhila et al, 2011]. In the present study, we found differential expression of miRNAs within families and miRNA arms between tissues and sexes in a teleost, which could result from target preference of miRNAs as it has been previously shown in mammals [Juhila et al, 2011].…”
Section: Sex-biased Expression Of Conserved Mirnassupporting
confidence: 85%
“…Similarly, several miRNA families were differentially expressed in 2 regions of mouse brain [Juhila et al, 2011]. In the present study, we found differential expression of miRNAs within families and miRNA arms between tissues and sexes in a teleost, which could result from target preference of miRNAs as it has been previously shown in mammals [Juhila et al, 2011]. Alternatively, it can be an effect of variation in post-transcriptional processing and in vivo accumulation or stability of miRNAs [Bail et al, 2010].…”
Section: Sex-biased Expression Of Conserved Mirnassupporting
confidence: 76%
“…General profiling by microarrays distinguished the differential expression of miRNAs in different regions of the rodent brain [49,50] with a specific emphasis on the cortex and hippocampus [51,52]. More recently, miRNA expression was also explored under conditions of elevated activity known to induce synaptic plasticity.…”
Section: Mirna Function In Synaptic Plasticity With Implications For mentioning
confidence: 99%
“…Approximately 50% of mammalian miRNAs are expressed in the brain (Krichevsky et al ., 2003; Somel et al ., 2011), many of which have critical roles in neurogenesis and neuronal development (Giraldez et al ., 2005; De Pietri Tonelli et al ., 2008). A number of hippocampal miRNAs regulate neuronal activity by targeting their downstream genes (Eacker et al ., 2011; Juhila et al ., 2011). For instance, in the miRNA‐mediated synaptic plasticity regulating pathway, miR501 (Hu et al ., 2015), miR223 (Harraz et al ., 2012) and miR134 (Jimenez‐Mateos et al ., 2012) target GluR1, GluR2 and NR2B, and DHX36, respectively.…”
Section: Introductionmentioning
confidence: 99%